Study of Peroxidase Catalysed Oxidation of Bisphenol a in Presence of Phenoxasine Derivative - Ivanec-Goranina, Rūta; Zazerskis, Pranas (Jaunųjų mokslininkų darbai, 2017)
Bisphenol A (Bis A) is notably harmful to human health, so research on its neutralisation is performed. Recombinant Coprinus cinereus peroxidase (rCiP) very slowly oxidises Bis A, but when 3-(10H-phenoxazin-10-yl) propionic acid (PPA) is added, oxidation speed increases. Bis A initial oxidation reaction rate dependences on the enzyme, substrate and mediator concentrations were established. PPA initial oxidation reaction rate dependence on the concentration of the mediator were established as well. Kinetic scheme for described processes was proposed. Kinetic characteristics were calculated from directly received data and modelling.
Keywords: peroxidase-catalysed oxidation; bisphenol A; phenoxasine derivative; mediator